Human milk oligosaccharides: bridging the gap in intestinal microbiota between mothers and infants - Sun, Wen; Tao, Lin; Qian, Chen; Xue, Pei-pei; Du, Si-si; Tao, Ying-na (Frontiers in Cellular and Infection Microbiology, 2025)
Breast milk is an essential source of infant nutrition. It is also a vital determinant of the structure and function of the infant intestinal microbial community, and it connects the mother and infant intestinal microbiota. Human milk oligosaccharides (HMOs) are a critical component in breast milk. HMOs can reach the baby’s colon entirely from milk and become a fermentable substrate for some intestinal microorganisms. HMOs can enhance intestinal mucosal barrier function and affect the intestinal function of the host through immune function, which has a therapeutic effect on specific infant intestinal diseases, such as necrotizing enterocolitis. In addition, changes in infant intestinal microbiota can reflect the maternal intestinal microbiota. HMOs are a link between the maternal intestinal microbiota and infant intestinal microbiota. HMOs affect the intestinal microbiota of infants and are related to the maternal milk microbiota. Through breastfeeding, maternal microbiota and HMOs jointly affect infant intestinal bacteria. Therefore, HMOs positively influence the establishment and balance of the infant microbial community, which is vital to ensure infant intestinal function. Therefore, HMOs can be used as a supplement and alternative therapy for infant intestinal diseases.